Interplay between Microorganisms and Geochemistry in Geological Carbon Storage - Kirk, Matthew F.; Altman, Susan J.; Santillan, Eugenio-Felipe U.; Bennett, Philip C. (My University, 2016)
Researchers at the Center for Frontiers of Subsurface Energy Security (CFSES) have conducted laboratory and modeling studies to better understand the interplay between microorganisms and geochemistry for geological carbon storage (GCS). We provide evidence of microorganisms adapting to high pressure CO2 conditions and identify factors that may influence survival of cells to CO2 stress. Factors that influenced the ability of cells to survive exposure to high-pressure CO2 in our experiments include mineralogy, the permeability of cell walls and/or membranes, intracellular buffering capacity, and whether cells live planktonically or within biofilm. Column experiments show that, following exposure to acidic water, biomass can remain intact in porous media and continue to alter hydraulic conductivity. Our research also shows that geochemical changes triggered by CO2 injection can alter energy available to populations of subsurface anaerobes and that microbial feedbacks on this effect can influence carbon storage. Our research documents the impact of CO2 on microorganisms and in turn, how subsurface microorganisms can influence GCS. We conclude that microbial presence and activities can have important implications for carbon storage and that microorganisms should not be overlooked in further GCS research.
Citation: Kirk, MF, Altman, SJ, Santillan, EFU, Bennett, PC (2016) Interplay between microorganisms and geochemistry in geological carbon storage. International Journal of Greenhouse Gas Control 47, 386-395.
Keywords: Carbon trapping; Porous media; Subsurface microbiology; Bioenergetics; Capnophile; Bioreactor experiments